An advanced course in air transport engineering - Hyde, David (College of Aeronautics, 1966)
In 1963 K.G. Wilkinson, then Assistant Chief Engineer of British European Airways, emphasised the lack of formal engineering education in the maintenance and operation of aircraft. This report describes the nine-month postgraduate-level course in Air Transport Engineering which was started in October, 1964 at The College of Aeronautics, Cranfield, in order to help in satisfying this requirement.